(17w-13)+(-6w+7)=

Simple and best practice solution for (17w-13)+(-6w+7)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (17w-13)+(-6w+7)= equation:


Simplifying
(17w + -13) + (-6w + 7) = 0

Reorder the terms:
(-13 + 17w) + (-6w + 7) = 0

Remove parenthesis around (-13 + 17w)
-13 + 17w + (-6w + 7) = 0

Reorder the terms:
-13 + 17w + (7 + -6w) = 0

Remove parenthesis around (7 + -6w)
-13 + 17w + 7 + -6w = 0

Reorder the terms:
-13 + 7 + 17w + -6w = 0

Combine like terms: -13 + 7 = -6
-6 + 17w + -6w = 0

Combine like terms: 17w + -6w = 11w
-6 + 11w = 0

Solving
-6 + 11w = 0

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 11w = 0 + 6

Combine like terms: -6 + 6 = 0
0 + 11w = 0 + 6
11w = 0 + 6

Combine like terms: 0 + 6 = 6
11w = 6

Divide each side by '11'.
w = 0.5454545455

Simplifying
w = 0.5454545455

See similar equations:

| .28x=700 | | x=-1.25y+3 | | 4.1x-17.49=2.6 | | (7w-13)+(-6w-7)= | | x-3=-1.25y | | f(-1)=4x-2x | | t+8t= | | f(2)=16x-2x | | 6x^2-84x+160=0 | | Y=-0.6(3)+0 | | 3sin^2x-3sinx-2=0 | | K+8=6(k-11) | | 14-2x=20-5x | | (10a+7)(3a-4)=0 | | 3y+15x=6 | | -8a+3a=15 | | 99=(w+2)(w) | | 6p-10q= | | f(-1)=16x-2x | | 5n-3=-188 | | 2b-3.4=-1.74 | | 121/8+f=194/5 | | c=50i^2+2000 | | f(0)=16x-2x | | 7(6-x)=-28 | | 6x^2-2x^2-2=-9x+1 | | 3.6=6.4-0.7X | | 8x-8=-136 | | 0=cos(4x) | | (fx)=4 | | 22.50=4g+3.54 | | f(x)=16x-2x |

Equations solver categories